Facebook And Instagram In Teaching Paragraph Writing: Students’ Perception - Murni Mahmud; Muftihaturrahmah Burhamzah; Akhmad Affandi (Seminar Nasional LP2M UNM, 2022)
Abstract. The purpose of this study was to explore the students’ perspectives regarding the use of Facebook and Instagram in writing paragraphs. This research is qualitative and used interview as the method in collecting data. The subject of the research is the English Literature students of the Faculty of Language and Literature, Universitas Negeri Makassar. Two classes were taken as the subject and they were taught paragraph writing during the semester. Representatives from the two classes were chosen as informants of the research to be interviewed. The results showed that English students of English Literature, Universitas Negeri Makassar gave positive perceptions about using Facebook and Instagram as a means of learning English, especially in writing paragraphs. Some advantages and strategies for using Facebook and Instagram in learning English are presented in this study. The findings from this research become important input for the students themselves in the university context and also as useful information among university practitioners so that they can utilize social media such as Facebook and Instagram at universities not only as communication tools but also as learning and teaching tools.